Clinical analysis of 175 cases of vaginal intraepithelial neoplasia - Dong, Hong; Li, Hongying; Wang, Liming; Yuan, Yuqin; Zhang, Dunlan; Zhou, Limin; Wang, Tinghui; Yang, Chunyan (European journal of obstetrics & gynecology and reproductive biology, 2023)
To evaluate the risk factors related to vaginal intraepithelial neoplasia (VaIN) severity. This retrospective study included patients with histologically confirmed VaIN diagnosed at Hubei Provincial Maternal and Child Health Hospital, China, between January 2017 and October 2021. The primary outcomes were persistence, remission, progression, and recurrence. Multiple ordinal logistic regression analysis was used to analyze the risk factors of VaIN severity. A total of 175 patients were included, 135 (77.1%) with VaIN 1, 19 (10.9%) with VaIN 2, and 21 (12%) with VaIN 3. Patients with VaIN 3 were older than those with VaIN1 2 (P < 0.001). The ratio of patients with concomitant cervical lesions increased with VaIN grade (23.7%, 47.4%, and 47.6% for VaIN 1, 2, and 3, respectively). The proportion of patients with intraepithelial neoplasia (CIN) 3 increased with the VaIN grade (3.1%, 44.5%, and 80% for VaIN 1, 2, and 3, respectively, respectively; all P < 0.001). In patients with VaIN 1, 19.4% had regression (spontaneous regression in 90.5%) and 80.6% underwent laser ablation (regression in 93.1%). In patients with VaIN 2 and 3, 3.1% showed no regression, 53.1% underwent laser ablation (regression in 76.4%), and 73.8% underwent excision (regression in 78.7%). Age (OR = 1.05, 95 %CI: 1.01–1.10, P = 0.010) and concomitant cervical lesion (OR = 6.99, 95 %CI: 2.31–21.12, P = 0.001) were independent risk factors for the severity of VaIN. Age and cervical lesions might be the risk factors for VaIN severity.